Case Report: Circulating Myeloid-Derived Suppressive-Like Cells and Exhausted Immune Cells in Non-Small Cell Lung Cancer Patients Treated With Three Immune Checkpoint Inhibitors - Bronte, Giuseppe; Verlicchi, Alberto; De Matteis, Serena; Rossi, Alice; Affatato, Alessandra; Sullo, Francesco Giulio; Gianni, Caterina; Canale, Matteo; Burgio, Marco Angelo; Delmonte, Angelo; Milella, Michele; Crinò, Lucio (Frontiers in Immunology, 2021)
Immune checkpoint inhibition induced a great step forward in the treatment of non-small cell lung cancer patients. In cancer immune microenvironment many checkpoints were studied and their involvement could represent a mechanism of resistance to cancer immunotherapy. For this reason the inhibition of multiple immune checkpoints is under development. However, myeloid-derived suppressor cells (MDSC) and exhausted immune cells could limit the efficacy of cancer immunotherapy. We analyzed the variation of circulating immune suppressive cell subsets in three non-small cell lung cancer patients treated with the combination of anti-CTLA-4 plus anti-PD-1 plus anti-LAG-3. We also describe the clinical and radiological course of the disease during this treatment in all three patients. We evaluated blood samples at three time points: T0 (baseline), T1 (after 2 months), T2 (after 4 months). We observed an increased mobilization of polymorphonuclear MDSC (CD15+HLA-DR-/lowCD11b+CD33+) and a reduction of monocytic MDSC (CD14+HLA-DR-/lowCD11b+CD33+) in peripheral blood. We also observed a boost of T, NK and NKT cells co-expressing PD-1 and LAG-3 at T2 during combination immunotherapy. These findings suggest that combination immunotherapy induces variation in the composition of immune suppressive cell subsets. The study on a wider patient population and experimental model design could help to clarify these findings.